Lumbar intervertebral disks: morphometric parameters and indices - Danylevych, V. P.; Guminskyi, Yu. Y.; Hryhorieva, O. A.; Danylevych, S.H.; Григор'єва, Олена Анатоліївна (My University, 2021)
An important element of evidence-based medicine is to take into account the individual variability of the indicators of the norm of intervertebral discs, which is undoubtedly the basis for early preclinical detection of their pathology. Mathematical modeling and comprehensive assessment of the parameters of the intervertebral discs can not only predict and determine the early manifestations of pathological changes, but also help to correct them in advance. The aim of the study was to calculate and evaluate the variability of absolute, calculated and relative metric parameters of intervertebral discs in the norm with the subsequent possibility of modeling standards based on individual linear dimensions of intervertebral discs of the lumbar spine and general anthropometric characteristics (body length and weight) in young men and men of the first period of adulthood (17-28 years), both in separate age groups and in the combined group. The series of MRI scans obtained on a Phillips Achieva 1.5T scanner measured the anterior, middle and posterior vertical dimensions, maximum sagittal and frontal dimensions of the intervertebral discs L1-L2, L2-L3, L3-L4, L4-L5 segments of the spine (IVDL1-L2, IVDL2-L3, IVDL3-L4, IVDL4- L5). We calculated the average height of the intervertebral discs, cross-sectional area and volume of intervertebral discs, as well as relative indicators - the ratio of the sum of sagittal and transverse dimensions, the sum of three dimensions, cross-sectional area and volume of intervertebral discs to the average intervertebral disc height. Statistical analysis of the obtained morphometric parameters was performed in the license package "STATISTICA 6.1". The distribution of variation series indicators, their average values and standard errors, coefficients of variation and asymmetry were evaluated. It was determined that the sums of the transverse and sagittal sizes and the sums of the three sizes increase proportionally in the caudal direction, have a distribution of indicators as close as possible to normal, and their coefficients of variation are many times smaller than for cross-sectional areas and volumes. Indicators of the ratio of the sum of the sagittal and transverse size and the sum of the three sizes to the average height of the intervertebral discs have a variability of less than 10% and correspond to the characteristics of the general population. Body weight and length have significantly higher correlation coefficients with the sums of sagittal and transverse dimensions, the sums of three dimensions and cross-sectional areas than with the partial dimensions of the intervertebral discs.
Keywords: intervertebral disc; lumbar spine; norm; somatometry; young men; men of the first period of adulthood